SEED FUNDING IN BIHAR: A COMPREHENSIVE LENS ON THE POLICY, INSTITUTIONAL AND CULTURAL ACCESS BARRIERS IN INDIA’S GROWING STARTUP LANDSCAPE - Swarup, Ranjan Kumar; Pratap, Kumar Alok (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Over the last two decades, the start-up/hyper-scale ecosystem in India has been to get to this levels backed by technology driven innovation, supportive government policy and the aspirations of the youth. Nonetheless, when looking at this growth at the state level, regional disparities become apparent, with states such as Bihar experiencing socio-economic, institutional, and cultural barriers that slow down the effective deployment of seed funding, which is a fundamental capital for early-stage startups. This study examines the potential challenges of seed funding within Bihar from a multifaceted perspective comprising of economic history, policy structures, institutional ecology and social mindset towards entrepreneurship. The paper identifies structural bottlenecks, such as bureaucratic inefficiencies, lack of industry-academia collaboration, and insufficient investor interest, which collectively stifle the growth of a robust startup culture in the state. Furthermore, the research highlights the role of cultural factors such as risk aversion, stigma of failure, and limited participation of women entrepreneurs as key barriers to innovation and capital utilization. The study argues for a systemic overhaul that combines policy reform, institutional strengthening, and cultural reorientation to foster an inclusive and sustainable entrepreneurial environment in Bihar.